2022
DOI: 10.1186/s42826-022-00124-5
|View full text |Cite
|
Sign up to set email alerts
|

A survey on the use of mice, pigs, dogs and monkeys as animal models in biomedical research in Spain

Abstract: Background The use of animals in biomedical science remains controversial. An individual’s level of concern is generally influenced by their culture, previous or current experience with animals, and the specific animal species in question. In this study we aimed to explore what people in Spain who had never or who no longer worked with laboratory animals thought of the use of mice, pigs, dogs and monkeys for biomedical research purposes. We also aimed to determine whether or not people currentl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 20 publications
1
11
0
1
Order By: Relevance
“…In this regard, we found that people working with small carnivores and non-human primates scored higher on TECA, a result that is not surprising in light of a recent survey in our country where the findings suggest that there is a difference in moral status between monkeys and dogs compared with pigs and mice. 16 Likewise, people working with small carnivores, farm animals and non-human primates reported more interaction with them. Although this was not the case in our study, it has been observed that human-animal interaction correlates positively with CS, 6,7 and may indicate that animal-facility personnel may take satisfaction from assuring laboratory animals' well-being and having a closer relationship with them.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, we found that people working with small carnivores and non-human primates scored higher on TECA, a result that is not surprising in light of a recent survey in our country where the findings suggest that there is a difference in moral status between monkeys and dogs compared with pigs and mice. 16 Likewise, people working with small carnivores, farm animals and non-human primates reported more interaction with them. Although this was not the case in our study, it has been observed that human-animal interaction correlates positively with CS, 6,7 and may indicate that animal-facility personnel may take satisfaction from assuring laboratory animals' well-being and having a closer relationship with them.…”
Section: Discussionmentioning
confidence: 99%
“…6,7,10,11,14,15 In Spain, the vast majority of people working with laboratory animals considered their job a socially sensitive issue but they believed that their work was justified. 12,16 Learning to cope with stress is critical. Maladaptive (passive) coping strategies are regarded as harmful, 17 for example, substance abuse or denial of emotions, and have been linked to increased risk of BO.…”
Section: Introductionmentioning
confidence: 99%
“…There is some evidence that people have stronger negative reactions and greater moral concern toward the use of primates than to lower-status animals used for food, such as the pig. 26,27 Primates seem to have greater intelligence; emotions that humans can identify with; look more human than other animals; and possess other traits that humans can relate tothis moral concern is likely rooted in our phylogenetic proximity. Many in society would likely have grave concerns about the killing of primates in large numbers to act as organ donors for humans, and there remains continued unease about their use in many scientific endeavors.…”
Section: The Use Of Animals As Sources Of Xenograftsmentioning
confidence: 99%
“…It is not entirely clear in the existing literature what specifically the public and medical community found objectionable. There is some evidence that people have stronger negative reactions and greater moral concern toward the use of primates than to lower‐status animals used for food, such as the pig 26,27 . Primates seem to have greater intelligence; emotions that humans can identify with; look more human than other animals; and possess other traits that humans can relate to—this moral concern is likely rooted in our phylogenetic proximity.…”
Section: The Use Of Animals As Sources Of Xenograftsmentioning
confidence: 99%
“…It is not limited solely to experimental procedures, but rather also encompasses the transport, husbandry, and euthanasia of animals [ 9 ]. Recently, we observed that people who work with laboratory animals are clearly aware of this and show great sensitivity to their well-being [ 10 , 11 ]. Moreover, perceived animal stress/pain negatively affects the professional quality of life of people working with laboratory animals [ 12 ].…”
Section: Introductionmentioning
confidence: 99%